2018
DOI: 10.1186/s13034-018-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of attachment relationship in adolescents’ problem behavior development: a cross-sectional study of Kenyan adolescents in Nairobi city

Abstract: BackgroundThere is a significant link between insecure attachment and the development of psychopathology in adolescence. We investigated the relationship between adolescent attachment styles and the development of emotional and behavioral problems among adolescents in Kenya. We also examined the modifying influence of socio-economic-status (SES).MethodOne hundred and thirty-seven adolescents who were attending two schools participated in the study. One school (low SES school) catered for children from predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…According to Wambua, Obondo, Bifulco and Kumar, (2018), authoritarian parenting style exudes warmth and structure in parenting which is in line with the findings of this study. This parenting style has a leaning towards being the optimal parenting style, which results in positive adolescent development.…”
Section: Issn: 2664-0112supporting
confidence: 90%
See 1 more Smart Citation
“…According to Wambua, Obondo, Bifulco and Kumar, (2018), authoritarian parenting style exudes warmth and structure in parenting which is in line with the findings of this study. This parenting style has a leaning towards being the optimal parenting style, which results in positive adolescent development.…”
Section: Issn: 2664-0112supporting
confidence: 90%
“…Additionally, the respondents were asked whether their parents always set limits in all that that they do and insist on obedience, 34.3% of the respondents strongly agreed, 31.3% agreed, 9.0% were undecided, 19.4% disagreed, and 6.0% strongly disagreed. Akin to these findings, Wambua et al (2018) found out that parental monitoring has an association with delinquent behavior. When parents have close ties with their children, they tend to set limits on what they do.…”
Section: Issn: 2664-0112mentioning
confidence: 87%
“…A plausible mechanism linking depressive symptoms to HRB clustering is experience of early childhood adverse life events. Indeed, Kenyan studies have found that adolescents who experienced adverse events such as extreme household poverty, living with caregivers who abuse substances, living with sick caregivers and experience of family conflict were more likely to engage in various forms of delinquent and health risk behavior [ 45 , 73 , 74 ], as well as experience psychological problems like anxiety and depression [ 74 , 75 ]. These findings highlight the need for inclusion of the prevention and management of common mental health disorders in interventions addressing HRB.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a transitional and critical developmental period in humans that is characterized by brain and body maturation, increased socialization, improvements in abilities, and the transition to independence [ 4 ]. During this period, poor mental health can compromise adolescents' development and future potential [ 5 ]. In recent years, a high prevalence of depression and anxiety symptoms has been reported worldwide, and there is increasing concern about the mental health of adolescents [ 6 , 7 ].…”
mentioning
confidence: 99%